Prolonged QT Syndrome Presenting as Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Two patients, ages 19 and 12 years, and a review of 8 previous cases of prolonged QT syndrome presenting as epilepsy are reported from the Department of Neurology and Hospital for Joint Diseases Epilepsy Center, New York University, New York.